Cover Feature: Total Synthesis, Stereochemical Revision, and Biological Assessment of Iriomoteolide‐2a (Chem. Eur. J. 36/2019). Issue 36 (17th May 2019) - Sakamoto, Keita; Hakamata, Akihiro; Iwasaki, Arihiro; Suenaga, Kiyotake; Tsuda, Masashi; Fuwa, Haruhiko
Abstract : Total synthesis of the proposed structure of iriomoteolide‐2 a revealed non‐identity with the natural product. Synthesis and detailed NMR spectroscopic analyses of candidate diastereomers enabled correction of the relative configuration of the proposed structure. Chiral HPLC analysis of a synthetic pair of enantiomers with authentic reference finally established the absolute configuration of iriomoteolide‐2 a. Biological assessment of the synthetic compounds was carried out to test the potency of this natural product. More information can be found in the Full Paper by H. Fuwa et al. on page 8528 .